RAYLEIGH-PLATEAU INSTABILITY STUDY FOR DROPLET FORMATION IN Y-JUNCTION AND T-JUNCTION MICROCHANNELS USING BIOFUELS - Yuwazama, Zido
Y-junction and T-junction microchannels are most commonly used in droplet formation. Droplet formation is caused by the phenomenon of Rayleigh-Plateau instability. Research about droplet formation using biofuels has not been widely conducted. Biofuels have great potential as renewable energy to replace fossil fuels. This study aims to observe droplet formation from Rayleigh-Plateau instability and investigate the pressure drop in Y-junction and T-junction microchannels using biofuels. Palm oil and V-Power Diesel as biofuels were used for droplet formation experiments due to their unique physical properties and chemical contents. Palm oil and V-Power Diesel have interfacial tensions with water of 9.2 mN/m and 20.9 mN/m with viscosities of 49.74 mPa.s and 1.97 mPa.s respectively. Y-junction and T-junction microchannels used in the experiment have diameters of 2.78 mm and 2.86 mm respectively. The contact angles used in the experiments were 90 degrees for the Y-junction microchannels and 180 degrees for the T-junction microchannels. The flow rate of both oil flows as dispersed phases was used at 3 mL/min, 6 mL/min, 9 mL/min, and 12 mL/min. The water flow rate as a continuous phase was set constant of 15 ml/min. Observation of droplet formation was conducted using a high-speed camera and macro lens. The length of the droplets formed from Rayleigh-Plateau instability depends on the flow rate ratio, type of connection, viscosity, and interfacial tension between oil and water. The length of the droplets obtained was between 3.0-5.4 mm. The increase in the length of the droplets was linear to the increase in the ratio of oil and water flow rates. The pressure drop in the microchannel in the palm oil experiment was between 171.0243-779.6140 Pa. While the pressure drop in the V-Power Diesel experiment in the microchannel was between 12.4587-29.0704 Pa. The results of the pressure drop in the droplet formation experiment from Rayleigh-Plateau instability showed results similar to the Poiseuille Equation.